ANALYSIS OF THE CANCELLATION OF CONSUMER DISPUTE SETTLEMENT DECISION BOARD SURABAYA NUMBER: 25/BPSK/XI/2020: A Case Study of Surabaya District Court Decision Number: 1212/Pdt.Sus.-BPSk/2020/PN.Sby. - Regina, Mariska; Munawaroh, Siti (YURIS: Journal of Court and Justice, 2023)
The Consumer Dispute Settlement Board (BPSK) is one of the institutions tasked with resolving consumer disputes. This research aims to find out the existence of BPSK can be part of equitable justice, especially for consumers who have suffered losses by business people because disputes between consumers and business people are usually small nominal so that consumers are reluctant to file disputes in court because it is not comparable between the cost of the case and the amount of losses experienced. The method used in this research is the juridical normative method. This is based on the consideration that the specification of this research is descriptive analytical, that is, describing existing legal problems based on applicable laws and regulations associated with legal theories and cases of consumer disputes which are the subject matter of the research. The results of this research, such as (1) the main task of BPSK is to resolve disputes between consumers and business actors; (2) Surabaya District Court Decision Number: 1212/Pdt.Sus.-BPSK/2020/PN.Sby., which canceled the Surabaya City BPSK Decision Number: 25/BPSK/XI/2020, according to researchers, this decision was right. One of the reasons that can be used to cancel the decision is the consideration of the judge who accepted the applicant’s reason that there was no legal relationship between the applicant and the respondent.